PENGARUH HERBISIDA PARAQUAT TERHADAP FEKUNDITAS DAN DAYA TETAS TELUR CACING TANAH (Lumbricus rubellus) - Novita, Emilia; Nurhadi, Nurhadi; Widiana, Rina (Pendidikan Biologi, 2013)
ABSTRACTÂ Earth-worm is an invetebrate animal which has many functions in other creatureâ lives, such as: to improve soil fertility, to be medicines, food, and cosmetics. But, the population of this creature is being threathened to decrease dractically because of the effect of any poisonous chemical subtances herbicide paraquat for instance. In line with this case, it has been done a research about the Effect of Â Herbicide Paraquat Towards Fecundity and Lay Rate of Â Earth- worm eggs (Lumbricus rubellus). This research was an experimental research. Treatment concentrations which werw done in this research were 0 %, 0,1 %, 0,2 %, 0,3 % and 0,4 %. TheÂ  dataÂ  in Â this Â research Â was Â gotten Â through Â various Â analysis Â and Â continued Â with Â the advanced test DNMRT. From this research, it was found that the number of production and lay rate of earth-worm cocon for every treatment which was given herbicide paraquat from the highest concentrations were different with the Â number o production and lay rate or earth- worm cocon which was not given herbicide paraquat. In analyzing the data in this research, it was found that F count > F table standard Î± 5 so that it can be concluded that herbicide paraquat which was sprayed into earth-worm food cause the fecundity and lay rate of earth-worm cocon (Lumbricus rubellus) to decrease. It is suggested from the result of this research that people should not use herbicide paraquat because it can decrease the fecundity and lay rate of earth-worm cocon.Â